Forms of Social Justice in The Anthropocene Era - Cicilia Damayanti (International Journal of Indonesian Philosophy & Theology, 2023)
In the Anthropocene period, justice is an urgent issue that necessitates a multifaceted strategy that tackles the numerous facets of social and environmental injustice. The Anthropocene epoch has resulted in enormous changes in the natural world, and the pursuit of justice must consider the intricacies of this new epoch. Degrowth, postcolonialism, and solidarity politics are crucial notions that might help us comprehend justice in the Anthropocene. For sustainability and social fairness, degrowth emphasizes lowering consumption and output. Postcolonialism exposes the continuous exploitation of underprivileged groups and emphasizes the need for equal resource allocation. Solidarity politics acknowledge community interconnectedness and the need for collective action in attaining justice. This essay focuses on the subject of social justice in the Anthropocene era. This essay uses the book's analysis techniques to investigate these ideas from the perspective of justice in the Anthropocene. The study's findings highlight the critical role that degrowth, postcolonialism, and solidarity-based politics may play in creating equity of justice for everyone. Investigating these subjects in creating a more egalitarian and sustainable society was emphasized in this essay.